THE IMAGE OF A WOMAN IN THE PRIMARY RELIGIOUS REPRESENTATIONS OF THE PEOPLES OF CENTRAL ASIA - Alimova F. Makhfuza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Before the introduction of the Islamic religion into Central Asia, the role of women in society in this region was radically different from that of other places. They actively influenced historical processes, played an important role in political life, and were also engaged in state affairs, military activities, and Economic Affairs. In historical sources, the names of the ruling women and soldiers also come.